Peranan Polisi Dalam Penyidikan Pelaku Tindak Pidana Pembunuhan Pengemudi Transportasi Online - Lubis, Muhammad Ridwan (Universitas Medan Area, 2024)
The role of the police in uncovering the perpetrators of murder is very important, for example in the case of the murder of an online transport driver. The police succeeded in arresting the perpetrators based on the investigation of the crime scene. Revealing the criminal act of murder of an online transport driver, the police carried out an investigation and investigation into this criminal act. The research carried out is empirical research. The data used is primary data and the data collection methods used in this research are library research and field research. The data analysis used is qualitative data. Disclosure of the criminal act of murder of an online transport driver by the police as investigators is an effort to obtain information through evidence and evidence, in order to gain confidence in whether the alleged criminal act is true or not and to determine whether there is any guilt in the suspect's person and for the benefit of For this proof, it is very necessary to have objects related to a crime, such as tools used to commit murder.